2021
DOI: 10.1002/cnr2.1517
|View full text |Cite
|
Sign up to set email alerts
|

Lack of knowledge regarding HPV and its relation to oropharyngeal cancer among medical students

Abstract: Background: Oropharyngeal cancer (OPC) is an important cause of cancer-related mortality. Early detection of OPC results in a favorable prognosis and higher survival rates. Infection by high-risk types of human papillomavirus (HPV) is a risk factor for OPC with an upward trend globally. Medical students' knowledge and awareness of HPV-related OPC can be crucial in the preventive efforts.Aim: To assess HPV knowledge among medical students at the University of Jordan, with particular focus on its relation to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
(90 reference statements)
1
7
0
Order By: Relevance
“…This might be related to the gradual acquisition of knowledge and skills over their years of study, which was evident by the results of this study for the majority of HIV knowledge items. Higher levels of knowledge among clinical students compared to their pre-clinical counterparts were also reported in recent studies addressing HPV knowledge among medical and dental students in Jordan and Saudi Arabia [ 33 , 34 , 72 ]. A similar pattern was observed among medical students in Israel and Malaysia and was attributed to the progressive exposure to more medical information (including those pertinent to HIV/AIDS) by advancing through curriculum years [ 41 , 73 ].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This might be related to the gradual acquisition of knowledge and skills over their years of study, which was evident by the results of this study for the majority of HIV knowledge items. Higher levels of knowledge among clinical students compared to their pre-clinical counterparts were also reported in recent studies addressing HPV knowledge among medical and dental students in Jordan and Saudi Arabia [ 33 , 34 , 72 ]. A similar pattern was observed among medical students in Israel and Malaysia and was attributed to the progressive exposure to more medical information (including those pertinent to HIV/AIDS) by advancing through curriculum years [ 41 , 73 ].…”
Section: Discussionsupporting
confidence: 65%
“…Finally, previous studies among college students in the MENA region have shown severe gaps in knowledge regarding STIs in general and HIV/AIDS in particular [ 33 , 56 , 57 ]. Therefore, the assessment of HIV/AIDS knowledge and the stigmatizing attitude towards PLWHA appears invaluable as an initial step to tailor well-informed actions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usual education and education for healthcare personnel should address gender prejudice. It is possible to increase vaccination rates by implementing systems-level methods, such as policy, that make vaccination recommendations routine [ 19 , 37 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Malaysia, 53.7% of medical students stated HPV as a risk factor for oral cancer [10]. In Jordan, 84.8% of medical students stated that HPV poses a risk for cervical cancer and 21.0% for oropharyngeal cancer [19]. In a study conducted with university students in the USA, 82% of the students noted HPV as a risk factor for cervical cancer and 24% for head and neck cancer [17].…”
Section: Discussionmentioning
confidence: 99%